Influence of light emitting diode (LED) on microalgae - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus (Universiti Malaysia Pahang, 2019)
There are 150,000 microalgae species. Scientists identified and classified 30,000 species. Only 10–15 species are utilised and studied for wastewater treatment, biogas upgrading, biomass production, and lipid content. LED can raise microalgae performance to the highest. Therefore, numerous empirical investigations have discussed for years about using various circumstances like light intensity, dark: light ratio, and wavelength. Though, studies have not discovered the ultimate LED for achieving maximum growth. Thus, this mini-review article shows the recent conducted studies on various microalgae species under LED impact to discover a range of optimal conditions. Besides, future perspective presents the next stage of research and development on using LED for microalgae growth.